Simultaneous measurement of strain and temperature based on fiber sensor with Vernier effect. (January 2023) - Zhao, Li; Hao, Shuai; Chen, Yunhao; Zhao, Enming; Xing, Chuanxi; Fan, Jing; Tang, Jianing
Highlights: The Vernier effect sensor could measure temperature and strain simultaneously. MZI and FPI of the Vernier effect sensor have different responses to temperature and strain. The MZI and FPI are highly symmetrical in structure, which are easy to fabricate and low in cost. Abstract: A fiber sensor based on Vernier effect for simultaneous temperature and strain measurement is proposed and demonstrated, which consists of a Mach-Zehnder interferometer and a Fabry-Perot interferometer. The two fiber interferometers are highly symmetrical in structure, both contain a hollow core fiber. The interferometer with a hollow core fiber of larger air hole diameter serves as the Fabry-Perot interferometer, and the other one with a hollow core fiber of smaller air hole diameter functions as the Mach-Zehnder interferometer. The Mach-Zehnder interferometer was found to be sensitive to temperature as well as strain, whereas the Fabry-Perot interferometer was only sensitive to strain variation. Due to the different response of two interferometers, the sensor achieved simultaneous measurement of temperature and strain. Leveraging on the Vernier effect and with MZI served as the sensing unit, the sensor provided a temperature sensitivity of −  279.99 pm /℃ and a strain sensitivity of −  5.95 pm/με, respectively. While using Fabry-Perot interferometer as the sensing unit, the sensor showed an enhanced strain sensitivity of 19.17 pm/με.